(untitled) (Bangladesh Veterinarian, 2013)
Humoral immune responses to Newcastle Disease Virus (NDV) and Bangladesh Agricultural University (BAU) Fowl cholera (BAUFC) vaccines were evaluated in naked neck chickens (NNC). Ten birds were vaccinated with Baby Chick Ranikhet Disease Virus (BCRDV) at Day 7 through intra-ocular route and with Ranikhet Disease Virus (RDV) at day 35 of age through intramuscular route. Serum antibodies were measured by Haemagglutination Inhibition test. Two weeks after final immunization all birds were challenged with virulent field isolate of NDV where all vaccinated birds survived without illness during ten days, and all ten control birds died. Ten birds were vaccinated with BAUFC vaccine at Day 42 and 70 according to the Manufacturers instruction, which induced detectable levels of antibody titre as determined by Passive Haemagglutination Assay (PHA) test. Eight vaccinated birds survived following challenge with virulent fowl cholera isolate two weeks after final vaccination and all ten control birds died. DOI: http://dx.doi.org/10.3329/bvet.v29i2.14342 Bangl. vet. 2012. Vol. 29, No. 2, 49-55